Barriers of Exporting Food Products for Micro, Small and Medium Enterprises in the Malang Greater Region of Indonesia: A Literature Study (Journal of Namibian Studies : History Politics Culture, 2023)
Micro, Small and Medium Enterprises (MSME) in Indonesia totaling around 64,200,000 contribute to economic growth of 8,575.89 trillion Rupiah, providing employment opportunities and strong output principles. The East Java region, which is part of Indonesia, has a total of 72,526 food and beverage processing MSMEs in Indonesia out of a total of 762,857 MSMEs located in the Malang Greater area. Malang Greater area Region which consists of the regions: 1. Malang City, 2. Batu City, 3. Malang Regency. MSMEs Malang Greater area, has many comparisons and outstanding achievements and has the potential to be made into an industry, has the potential to be exported. Nevertheless, very few exports 13.94% of the total export value of Indonesia in 2019, because there are barriers faced by MSMEs for export. There are many models of export barriers, in this Thesis using the Leonido export barrier classification model, this model was chosen because it is more systematic and comprehensive with 39 indicators and can be developed according to the actual problem faced by MSMEs. This indicator/indicator consists of query material and data processing using the SEM-PLS method. If MSMEs are allowed to export, many benefits will be obtained, including: reducing competition between similar MSME products in Malang Greater area, reflecting excessive power in providing financial benefits to MSMEs, developing markets, increasing foreign exchange, increasing life expectancy, increasing competitiveness, reduce domestic market applause and low profit domestic market. It is hoped that MSME food products will be allowed to be exported after all e-sports barriers are identified and data is processed and solutions are found instead of investigation results. The results of this investigation are expected to help remove barriers to the export of MSMEs, so that MSMEs can export directly or indirectly, the cooperation of the governments of Indonesia and East Java as well as Malang Greater area can provide guidance, help MSMEs to export food.